Biochemical Characterization and Analyses of Polysialic‐Acid‐Associated Carrier Proteins and Genes in Piglets during Neonatal Development. (5th June 2017) - Chen, Yue; Ren, He; Zhang, Nai; Troy, Frederic A.; Wang, Bing
Abstract: Polysialic acid plays a key role in cancer metastasis and neurodevelopment. Our aim was to determine the developmental gene‐expression profiles for the two polysialyltransferases ST8Sia II and ST8Sia IV, neural cell‐adhesion molecules (NCAMs), SynCAM 1, neuropilin‐2 (NRP2) and their polysialylated cognate glycans in different regions of the piglet brain during postnatal development. Our findings show that: 1) the cellular levels of mRNA coding for ST8Sia II and ST8Sia IV, NCAMs, SynCAM 1, NRP2 and polySia are age‐dependent and cell‐type‐specific during neonatal brain development, 2) there was a lack of correlation between abundance level of mRNA coding for ST8Sia II and ST8Sia IV and the abundance level of the post‐translation expression of polySia in all nine brain regions, 3) expression levels of polySia did not correlate with the levels of the carrier proteins NCAM‐140, SynCAM 1 and NRP2 in nine brain regions, and 4) the cellular abundance of ST8Sia II and ST8Sia IV in nine subregions of piglet brain is regulated at the level of translation/post‐translation, and not at the level of transcription. Collectively, our findings suggest that neuronal and glial cells within different regions of the brain have different transcriptional programs that can direct cell division at different rates based on the activity levels of ST8Sia II and ST8Sia IV and the level of their carrier proteins during neurodevelopment. Abstract : Developmental gene‐expression profiles for polysialic‐acid‐associated carrier proteins and genes as well as their polysialylated cognate glycans in different regions of the piglet brain during postnatal development suggest that neuronal and glial cells in different brain regions have different transcriptional programs that can direct cell division at different rates as determined by the activity levels of these species during neurodevelopment.